A blessing or curse: the spillover effects of city–county consolidation on local economies. Issue 9 (2nd September 2022) - Deng, Nanxin; Feng, Bo; Partridge, Mark D.
ABSTRACT: Previous studies suggest that 'city–county consolidation' has significant positive impacts on urban economic growth. Yet, the specific spillover effects on surrounding rural areas and the overall net impact on larger regions have not been fully investigated. We propose a difference-in-difference framework and find that consolidations have led to a significant loss of per capita gross domestic product (GDP) in nearby rural areas. The backwash mainly comes from the reduction of rural industrial output. We also find that this policy has an insignificant impact at the prefecture level, suggesting such consolidations do not promote aggregate growth and that any gains in urban areas are offset by losses in surrounding rural regions.